Clinical Tolerance of In-Neonatal Intensive Care Unit Administration of Rotavirus Vaccine - Briggs-Steinberg, Courtney; Aboudi, David; Hodson, Gabrielle; Shah, Shetal (American Journal of Perinatology, 2019)
Objective This article determines the tolerance of neonatal intensive care unit (NICU)-based administration of RV5 in premature infants. This article also aims to compare the rate of clinically significant adverse events after RV5 immunization to the standard 2-month shot series and to historical controls who were not immunized.Study Design This is a retrospective case–control study of 201 premature infants immunized with RV5. Infants were evaluated for clinically significant events 7 days before and after immunization and were compared with events after the 2-month shot series and to 189 historical controls. Wilcoxon signed rank test and McNemar's test were used for all paired analysis.Results There was no increase in number of infants with clinically significant adverse events when comparing after RV5 to prior to RV5, after the 2-month shot series, or to the historical controls.Conclusion RV5 is well tolerated in premature infants and does not result in clinically significant adverse events when administered in NICU-hospitalized infants.
Keywords: rotavirus; neonatal intensive care unit; premature; immunization